2014
DOI: 10.5489/cuaj.2037
|View full text |Cite
|
Sign up to set email alerts
|

Assessing radiation exposure during endoscopic-guided percutaneous nephrolithotomy

Abstract: Introduction: Percutaneous nephrolithotomy (PCNL) may be associated with significant ionizing radiation exposure for patients and operating room staff. Endoscopic-guided PCNL (ePCNL) is a technique that may be associated with less radiation exposure. This study examines ePCNL-related radiation exposure (fluoroscopy time, effective dose) and investigates variables that may predict increased exposure. Methods: A retrospective review of all consecutive ePCNLs performed at our institution, by a single surgeon, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…After positioning the ureteroscope in the target calyx of choice, fluoroscopy is used to guide a needle into the kidney in an antegrade percutaneous fashion and the needle enters the collecting system under direct vision of the ureteroscope. It can be performed either in a modified supine [ 18 ] or prone split-leg position [ 19 , 20 ]. Once a target calyx is identified by flexible ureterorenoscopy, fluoroscopy is still needed for caliceal puncture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After positioning the ureteroscope in the target calyx of choice, fluoroscopy is used to guide a needle into the kidney in an antegrade percutaneous fashion and the needle enters the collecting system under direct vision of the ureteroscope. It can be performed either in a modified supine [ 18 ] or prone split-leg position [ 19 , 20 ]. Once a target calyx is identified by flexible ureterorenoscopy, fluoroscopy is still needed for caliceal puncture.…”
Section: Discussionmentioning
confidence: 99%
“…Once a target calyx is identified by flexible ureterorenoscopy, fluoroscopy is still needed for caliceal puncture. Compared to standard PCNL, however, this technique can be associated with lower fluoroscopic screening time and increased stone clearance [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using visual and tactile cues, fixed lower mAs and kVp, a designated fluoroscopy technician on a laser-guided C-arm, and pulsed fluoroscopy at 1 frame per second was associated with 80.9% reduction in FT during PCNLs (175.6 vs. 33.7 s; p < 0.001) [15] . Finally, endoscopic-guided PCA has been recently described to be associated with significantly lower FT during PCNL [16] , [17] .…”
Section: Discussionmentioning
confidence: 99%
“…The BTA-TRAK and BTA-stat kits have a sensitivity of around 65% and specificity of 74–77% [ 13 , 52 ]. A meta-analysis of 13 studies that reviewed 3175 patients found the sensitivity and specificity of the BTA-stat kit to be 64–69% and 73–77%, respectively [ 9 ]. However, the studies included in this meta-analysis mainly compared individuals with high-grade UC with control groups.…”
Section: Fda-approved and Investigational Uc Biomarkersmentioning
confidence: 99%